Exploring Ethnobotanical Knowledge: Qualitative Insights into the Therapeutic Potential of Medicinal Plants - Muhajirin Dean (Manunggal Halim Jaya, 2024)
The study's primary aim is to systematically document and analyze the ethnobotanical knowledge of indigenous communities, emphasizing integrating this knowledge into modern medical practices and conservation efforts. The research methodology encompasses a qualitative approach, utilizing in-depth interviews, participant observations, and the collection of personal narratives from various Indigenous groups. These methods facilitate a comprehensive understanding of medicinal plants' traditional uses and cultural values, ensuring a respectful and accurate representation of indigenous knowledge. Findings reveal that medicinal plants are crucial for health and deeply ingrained in communities' social and spiritual fabric. The study highlights the importance of sustainable practices and the risks of cultural erosion and biodiversity loss due to modernization and environmental degradation. Key insights point towards the potential of integrating traditional medicinal knowledge with contemporary healthcare systems, which could foster innovative therapeutic practices and enhance global health sustainability. The research underscores the urgent need for conservation strategies that involve local communities and respect their intellectual property and cultural heritage. The results advocate for policy development that supports the inclusion of traditional remedies in national health systems, thus preserving invaluable knowledge and promoting a more holistic approach to health.